Clinico-pathological profile of nasopharyngeal carcinoma at Muhimbili National Hospital, Dares Salaam, Tanzania - Abraham, Zephania Saitabau; Massawe, Enica Richard; Ntunaguzi, Daudi; Kahinga, Aveline Aloyce; Yahaya, James Joseph; Mithe, Siwillis Elizabeth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Nasopharyngeal carcinoma (NPC) is an uncommon malignant tumor which has been reported invariably and cases have been encountered in Tanzania. Though rare they are associated with potential morbidity and mortality. The aim of this study was to characterize the clinico-pathological profile of such neoplasm in our set up. Methods: A retrospective review of 25 cases from hospital archives for 3 consecutive years was done where all patients with a histopathologically confirmed diagnosis of NPC were recruited. Data was analyzed using SPSS version 21. Results: Of the 25 eligible cases, 15 (60%) were males and 10 (40%) were females. Age range was 15-70 years. The peak age was 30-50 years in males and 50-59 years in females. Highest incidence was in the 5th decade. The commonest presenting features were cervical lymphadenopathy (92%) epistaxis (80%), hearing loss (80%) and nasal obstruction (76%) while the least common feature was seizures (4%). Histologically, undifferentiated carcinoma (76%) was the commonest variant while the least common one was differentiated non keratinizing squamous cell carcinoma (8%). Identifiable risk factors were consumption of salted smoked fish (80%), tobacco use (60%), alcohol intake (52%) and occupational exposure to wood dust (32%). Majority of patients (80%) were diagnosed with advanced stage of the disease (Stage IV). Conclusions: Findings from this study correlate with what has been reported elsewhere. Clinicians should have a higher index of suspicion in diagnosing NPC to enable early referral and prompt treatment of such malignant neoplasm.